OC-035 Streamlining immunosuppression therapy and improving the quality of care for ibd patients: a virtual immunosuppression clinic. (17th June 2017) - Kemp, K; Birchall, F; Dutton, H; Kirkbride, M; Brooks, J; Levison, S
Abstract : Introduction: Increasing demands on IBD services have led to innovations in the way we interact with and deliver care to patients. IBD teams must work proactively to develop an efficient and cost effective service that enhances a patient's experience. Optimising the care of our patients can incorporate direct or 'virtual' interactions. Method: To standardise and improve the care of IBD patients requiring immunosuppression therapy (Aza, 6-MP, MTX) we developed a weekly virtual immunosuppressant clinic (VIC). Irrespective of their referring consultant, any IBD patient commencing therapy in our large teaching hospital between 19/5/2016- 12/1/2017 was included. To streamline the workload, all patients requiring scheduled blood test monitoring with therapy were offered blood tests on a Tues/Weds. Patients were then phoned during the VIC on a Thursday evening and their dose adjusted as/if needed. The scheduling of the next blood tests, and the measurement of AZA metabolite levels at week 12, were co-ordinated via the VIC. Stable patients were then transferred to the GP, under a Shared-Care pathway. The tariff from the VIC phone call, the number of OPDs saved, and the costs incurred were calculated with the Specialist Medicine Informatics. The VIC was prospectively audited. Results: 70 patients were commenced on immunosuppressant therapy during the 8 months observed. During this time, 35 virtual clinics were held, averaging 13 calls per clinic (total calls=464). The income generated by the VIC tariff (£30 per VIC) was £13, 9200. This saved the CCG £39 904 if all patients had instead required face to face follow up. The VIC detected 28 patients with abnormal blood tests requiring dose adjustment (31.1%). The VIC detected 5 AZA shunters (5.6%) and identified 17 patients with drug related side effects requiring the cessation of therapy (18.9%). Conclusion: The co-ordination of patients' care through a weekly virtual immunosuppression clinic provides an efficient and effective forum for instigating therapy safely. The IBD service proactively works to delivery optimal care and reduce unnecessary outpatient appointments, whilst enhancing patient experience. Disclosure of Interest: None Declared